Optimizing the high-intensity interval session through workload alterations in well-trained female and male cyclists - Urianstad, T.; Odden, I.; Crantz Lorentzen, H.; Odden, I.; Mølmen, K. S.; Hamarsland, H.; Hammarstrom, D.; Rønnestad, B. R. (Journal of Science and Cycling, 2023)
High-intensity interval training (HIT) sessions with a variable workload during the work periods has been considered more effective compared to HIT sessions performed at a constant workload; the optimal HIT design is unknown. This study investigated the isolated effect of power output distribution during three specific HIT sessions, not influenced by factors such as different training duration and different mean power output. 19 well-trained female and male cyclists (age, 22.6 (4.1); maximal oxygen consumption (VO2max), 70.3 (11.0) mL·min-1·kg-1) performed three different 6x8-minutes HIT sessions at a mean power output corresponding to the individual participants´ 40-minute maximal power output (FTP) on three consecutive days, in a randomized order: Session 1) 8-minute work periods with 30-seconds work periods at 118% of FTP separated by 15-seconds recovery periods at 60% of FTP (30/15), Session 2) 8-minute work periods performed at a steady power output corresponding to 100% of FTP (CON), Session 3) 8-minute work periods performed as two continuously changing 60-seconds work periods at 110 and 90% of FTP, respectively (60/60). During the HIT sessions, both mean oxygen consumption (%VO2maxHIT) and time =90% of VO2max were higher in 30/15 compared to 60/60 (p=0.045 and p=0.042, respectively) and CON (p=0.001 and p=0.001, respectively). In conclusion, 30/15 led to a higher %VO2maxHIT and more accumulated time =90% of VO2max than both 60/60 and CON, suggesting that this HIT protocol provides the most effective training stimulus.